PERSEPSI KONSUMEN TERHADAP INTEGRATED CULINARY EXPERIENCE: ANALISIS PREFERENSI, MOTIVASI, DAN PERILAKU DI SEKTOR FOOD & BEVERAGE - Damayanti, Dita; Tjahyadi, Freddy; Sumawinata, Rara Inten; Syarif T. P, Ruswan; Simatupang, Parhimpunan (POLITEKNIK LP3I JAKARTA, 2026)
This study aims to examine a conceptual model explaining consumer perceptions of Integrated Culinary Experience (ICE) by analyzing the effects of motivational drivers, perceived premium attributes, and experiential value. The main research problem lies in the absence of an integrated model that explains how consumption motivation, premium attributes, and experiential value interact in shaping ICE perceptions within the premium ready-to-eat food sector. This research employs a quantitative explanatory approach. Data were collected through a survey using a Likert-scale questionnaire administered to 169 respondents in the Greater Jakarta area (Jabodetabek). Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS software. Hypothesis testing was based on path coefficients, t-statistics, and p-values obtained from bootstrapping procedures. The results indicate that consumer motivation has a positive and significant effect on ICE perception. Perceived premium attributes do not show a significant direct effect, while experiential value emerges as the strongest and most dominant factor influencing ICE perception. The findings suggest that urban consumers prioritize meaningful and immersive experiences, positioning premium attributes as hygiene factors. Practical implications highlight the importance of storytelling, presentation rituals, multisensory elements, and emotional and social experiences in premium F&B practices.